Expediente (Revista do Tribunal Regional Federal da 3ª Região, 2012)
DIRETOR DA REVISTADesembargador Federal Antonio CedenhoASSESSORWladimir RodriguesEQUIPELucia Massako Y. C. RosaMônica Maria Meloni SícoliRafael Leal FerreiraRenata Bataglia GarciaSimone de Alcântara Savazzoni